Preliminary evaluation of the biological state of rural population from the Kościerzyna region based on selected data on migration, fertility and mortality - Berdychowski, Włodzimierz; Henneberg, Maciej (Anthropological Review, 1978)
Kościerzyna region constitutes a southern part of the Casubian area situated on lower Vistula and around Gdańsk. The area is inhabited by about 300 000 autochtonous slavic people differing from surrounding Polish populace in some minor cultural traits (e.g. having special Casubian dialect). Some physical anthropologists have claimed that Casubians are also morphologically different from their neighbours. This implies that there are operating factors promoting and maintaining biological dissimilarity of those people to other groups. The most probable factors are those influencing genetic composition and structure — first of all isolation and natural selection. In order to find out the degree of isolation and opportunity for selection the authors have collected data on 165 married couples living in a number of villages in the vicinity of the town Koscierzyna. The average local group (inhabiting one settlement) of the region comprises about 50 - 60 adults in the reproductive ability life span. The data collected contain information on the places of birth of adults, their parents and their children, birth spacing, number of offspring in a family and subadult deaths. Those data were complemented by official published demographic information. From the analysis of distributions of distances between birthplaces of spouses (see fig. 2), of their parents (see fig. 3) and parents and offspring (see fig. 4) it follows that the isolation by distance, being in general of the type of two-dimensional isotropic migration, is very weak, local group endogamy rate is close to 0.25 both in the living generation of adults and in the previous one. A few percent of distances is longer than 100 kms. Coefficients of kinship estimated with the use of Malécot’s and Henneberg’s [1978] methods for local groups lie in the range 0.000017 - 0.00050 indicating practical lack of possibility of genetic drift or inbreeding effects. Estimated with use of Crow's indices opportunity for selection is small (Im =0.110, If=0.252, I=0.361). Opportunity for selection through differential mortality estimated with the use of Ibs index [Henneberg and Piontek, 1975] is similarly small (see tab. 3). Fertility, investigated with use of birth spacing analysis (length of birth intervals by age of women, see tab. 4) is similar to that observed in non-Malthusian populations, although, as is known from interviews, methods of birth control are known to the studied people and sporadically some kinds of contraception performed. Despite this fact differentiation of reproductive abilities of couples measured according to Henneberg's [1976] proposition does not differ from that observed among 19th century rural populace of Great Poland. In conclusion the authors state that there is no basis for maintaining that inhabitants of the studied region differ genetically from those of neighbouring areas, and practically from the majority of Polish population.